Returning Evidence to the Scene of the Crime: Why the Anfal Files Should be Repatriated to Iraqi Kurdistan - Montgomery, Bruce P. (Archivaria, 2010)
On 22 April 2008, five years after the American invasion of Iraq, the Society of American Archivists (SAA) and the Association of Canadian Archivists (ACA) issued a joint statement calling for American authorities to repatriate millions of captured intelligence documents and intervene with the “government of Kurdistan” to return the Iraqi Anfal files to the Iraq National Library and Archive in Baghdad. The Anfal files, which chronicle Iraq’s genocide against the Kurds during the mid- to late-1980s, were captured by Kurdish peshmerga in the March 1991 uprisings following the first Gulf War. They were transferred to the United States for safe storage and analysis for human rights crimes with the understanding that the documents were Kurdish property. The SAA and ACA based their statement on the archival principle of the inalienability of national records, a concept that claims that the alienation of national records can only occur through a legislative act of the state. This principle of inalienability, however, is incompatible with the laws of war that allow for the capture of state records during hostilities, conflicts with the international legal regime of human rights regarding the restitution of state security files to a repressive regime that may reuse them, and contradicts the original agreement between American and Kurdish authorities governing ownership of the Anfal files. Indeed, with the growing appearance of a new Iraqi repressive regime – with one faction ruling at the expense of the others – there is considerable danger in repatriating the Anfal files and Hussein’s archive of atrocity to the ruling theocrats in Baghdad before political reconciliation takes root. Reasons of historical patrimony and provenance also argue for the return of the Anfal documents to Iraqi Kurdistan. RÉSUMÉ Le 22 avril 2008, cinq ans après l’invasion américaine de l’Iraq, la Society of American Archivists (SAA) et l’Association of Canadian Archivists (ACA) ont émis une déclaration commune demandant aux autorités américaines de rapatrier les millions de documents du renseignement saisis et d’intervenir auprès du « gouvernement du Kurdistan » afin de retourner les dossiers de l’Anfal iraquien à la Iraq National Library and Archive, à Bagdad. Les dossiers de l’Anfal, qui documentent le génocide iraquien des Kurdes durant la deuxième moitié des années 1980, avaient été saisis par les peshmergas kurdes pendant les insurrections de mars 1991 suite à la première guerre du Golfe. Ils ont été transférés aux États-Unis pour entreposage sécuritaire et pour les analyses dans l’optique des crimes contre l’humanité, tout en demeurant propriété kurde. La SAA et l’ACA ont basé leur déclaration sur le principe archivistique de l’inaliénabilité des documents nationaux, concept qui affirme que l’aliénation des documents nationaux ne peut se faire que par un acte législatif de l’état. Ce principe de l’inaliénabilité, cependant, est incompatible avec les lois de la guerre qui permettent la saisie de documents d’état pendant les hostilités; il entre en conflit avec le régime légal international en matière de droits humains au sujet de la restitution des dossiers de sécurité d’état à un régime répressif qui pourrait s’en servir à nouveau; et il contredit l’entente d’origine entre les autorités américaines et kurdes au sujet du droit de propriété des dossiers de l’Anfal. En effet, étant donné l’apparence montée d’un nouveau régime répressif en Iraq – avec une faction qui gouverne au détriment des autres – il y a un danger considérable de rapatrier les dossiers de l’Anfal et les archives des atrocités d’Hussein aux théocrates au pouvoir en Iraq avant qu’aucune réconciliation politique n’ait pu s’enraciner. Les notions de patrimoine historique et de provenance encouragent aussi le retour des documents de l’Anfal au Kurdistan iraquien.
Other Publications

Archivos y derechos humanos en América. La Corte Interamericana de Derechos Humanos - Arias, Virginia (Comma, 2010)
Other Publications

Of condors and judges: Archival musings over a judicial investigation - Barrera, Giulia (Archival Science, 2010)
(2010) Barrera. Archival Science. Abstract The paper discusses some archival issues that emerged during a judicial investigation carried out by the Prosecutor’s Office\nof Rome (Italy) regarding h...
Other Publications

Los Archivos de Derechos Humanos en Perú - Cruz, Ruth (Comma, 2010)
Other Publications

Archives against Amnesia - Peterson, Trudy Huskamp (Politorbis., 2010)
Other Publications

Sites of Conscience: New Approaches to Conflicted Memory - Ševčenko, Liz (Museum International, 2010)
For better or for worse, heritage is a key terrain on which societal conflicts are expressed. Instead of treating conflict over heritage sites defensively, shielding them from attack, we can take proactive steps to offer heritage sites as resources for addressing contested social questions. This article explores strategies used around the world by ‘Sites of Conscience’– heritage sites that foster dialogue on contemporary issues – to help communities to confront the questions that divide them.
Other Publications

The Universal Declaration on Archives - International Council on Archives (2010)
Adopted at the General Assembly of ICA Oslo, September 2010. Endorsed by the 36th Session of the General Conference of UNESCO on 10th November 2011.

Transitional Justice in Eastern Europe and the former Soviet Union: Reckoning with the communist past - Stan, Lavinia (Routledge, 2010)
During the last two decades, the countries of Eastern Europe and the former Soviet Union have attempted to address the numerous human rights abuses that characterized the decades of communist rule. This book examines the main processes of transitional justice that permitted societies in those countries to come to terms with their recent past. It explores lustration, the banning of communist officials and secret political police officers and informers from post-communist politic, ordinary citizens’ access to the remaining archives compiled on them by the communist secret police, as well as trials and court proceedings launched against former communist officials and secret agents for their human rights trespasses. Individual chapters explore the progress of transitional justice in Germany, the Czech Republic, Slovakia, Poland, Hungary, Romania, Bulgaria, Albania, Slovenia and the successor states of the former Soviet Union. The chapters explain why different countries have employed different models to come to terms with their communist past; assess each country’s relative successes and failures; and probe the efficacy of country-specific legislation to attain the transitional justice goals for which it was developed. The book draws together the country cases into a comprehensive comparative analysis of the determinants of post-communist transitional justice, that will be relevant not only to scholars of post-communist transition, but also to anyone interested in transitional justice in other contexts.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Sorry States: Apologies in International Politics - Lind, Jennifer (Cornell University Press, 2010)
Governments increasingly offer or demand apologies for past human rights abuses, and it is widely believed that such expressions of contrition are necessary to promote reconciliation between former adversaries. The post-World War II experiences of Japan and Germany suggest that international apologies have powerful healing effects when they are offered, and poisonous effects when withheld. West Germany made extensive efforts to atone for wartime crimes-formal apologies, monuments to victims of the Nazis, and candid history textbooks; Bonn successfully reconciled with its wartime enemies. By contrast, Tokyo has made few and unsatisfying apologies and approves school textbooks that whitewash wartime atrocities. Japanese leaders worship at the Yasukuni Shrine, which honors war criminals among Japan's war dead. Relations between Japan and its neighbors remain tense.Examining the cases of South Korean relations with Japan and of French relations with Germany, Jennifer Lind demonstrates that denials of past atrocities fuel distrust and inhibit international reconciliation. In Sorry States, she argues that a country's acknowledgment of past misdeeds is essential for promoting trust and reconciliation after war. However, Lind challenges the conventional wisdom by showing that many countries have been able to reconcile without much in the way of apologies or reparations. Contrition can be highly controversial and is likely to cause a domestic backlash that alarms?rather than assuages?outside observers. Apologies and other such polarizing gestures are thus unlikely to soothe relations after conflict, Lind finds, and remembrance that is less accusatory-conducted bilaterally or in multilateral settings-holds the most promise for international reconciliation.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Gacaca Courts, Post-Genocide Justice and Reconciliation in Rwanda: Justice without Lawyers - Clark, Phil (Cambridge University Press, 2010)
This is a timely empirical study and review of the Gacaca Courts which were established in 2001 in Rwanda as an attempt to prosecute suspects involved in the 1994 genocide. Based on the author's original field work which began in 2003 in Rwanda and which has been updated to the end of 2009, it includes responses from within the Rwandan population. Dr. Clark argues that, despite widespread international scepticism, the Gacaca process has achieved remarkable results in terms of justice and reconciliation, although this has often come at a price, especially the re-traumatisation of many Rwandans who have participated firsthand in hearings. This book will appeal to a wide global readership crossing human rights, transitional justice and African studies for its combination of original empirical data with a socio-legal analysis.
Keywords: References - Boel et al. (2021); Archives and Human Rights

State Coordinated Violence in Chad under Hissène Habré - Silva, Romesh; Klingner, Jeff; Weikart, Scott (Human Rights Data Analysis Group, 2010)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Unspeakable Truths: Transitional Justice and the Challenge of Truth Commissions - Hayner, Priscilla B. (Routledge, 2010)
In a sweeping review of forty truth commissions, Priscilla Hayner delivers a definitive exploration of the global experience in official truth-seeking after widespread atrocities. When Unspeakable Truths was first published in 2001, it quickly became a classic, helping to define the field of truth commissions and the broader arena of transitional justice. This second edition is fully updated and expanded, covering twenty new commissions formed in the last ten years, analyzing new trends, and offering detailed charts that assess the impact of truth commissions and provide comparative information not previously available.Placing the increasing number of truth commissions within the broader expansion in transitional justice, Unspeakable Truths surveys key developments and new thinking in reparations, international justice, healing from trauma, and other areas. The book challenges many widely-held assumptions, based on hundreds of interviews and a sweeping review of the literature. This book will help to define how these issues are addressed in the future.
Keywords: References - Boel et al. (2021); Archives and Human Rights

International Convention for the Protection of All Persons from Enforced Disappearance - OHCHR (2010)
Entry into force: 23 December 2010, in accordance with article 39(1) which reads as follows: “This Convention shall enter into force on the thirtieth day after the date of deposit with the Secretary-General of the United Nations of the twentieth instrument of ratification or accession.”. Preamble The States Parties to this Convention,
Keywords: References - Boel et al. (2021); Archives and Human Rights

Austerlitz - Sebald, W.G. (Penguin, 2010)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Emergence of Memory: Conversations with W. G. Sebald - Sebald, W. G. (Seven Stories Press, 2010)
When German author W. G. Sebald died in a car accident at the age of fifty-seven, the literary world mourned the loss of a writer whose oeuvre it was just beginning to appreciate. Through published interviews with and essays on Sebald, award-winning translator and author Lynne Sharon Schwartz offers a profound portrait of the writer, who has been praised posthumously for his unflinching explorations of historical cruelty, memory, and dislocation. With contributions from poet, essayist, and translator Charles Simic, New Republic editor Ruth Franklin, Bookworm radio host Michael Silverblatt, and more, The Emergence of Memory offers Sebald’s own voice in interviews between 1997 up to a month before his death in 2001. Also included are cogent accounts of almost all of Sebald’s books, thematically linked to events in the contributors’ own lives.Contributors include Carole Angier, Joseph Cuomo, Ruth Franklin, Michael Hofmann, Arthur Lubow, Tim Parks, Michael Silverblatt, Charles Simic, and Eleanor Wachtel.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Annual report of the Inter-American commission on human rights 2009. Report of the special rapporteur for freedom of expression. - Marino, Catalina Botero (Inter-American Commission on Human Rights, 2010)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

ISO/TS 21547:2010 - Health informatics — Security requirements for archiving of electronic health records — Principles - ISO (ISO, 2010)
Health informatics — Security requirements for archiving of electronic health records — Principles
Keywords: References - Comma (2020 1-2); Archives and Human Rights

JFS Brochure - N.C. Justice for Sterilization (N.C. Justice for Sterilization, 2010)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Declaration on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities - United Nations Human Rights (United Nations, 2010)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Expert Meeting - The Concept of Stateless Persons under International Law - Summary Conclusions - United Nations High Commissioner for Refugees (United Nations, 2010)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

The Nuremberg Laws - Dferriero (National Archives, 2010)
Last Wednesday, I visited the Huntington Library in California to receive the original Nuremberg Laws on behalf of the U.S. Government. The laws were signed by Adolf Hitler and issued by the Third …
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Open letter to Spanish judiciary authorities in solidarity with Justice Baltasar Garzón - Human Rights Defenders (International Federation for Human Rights, 2010)
Judges of the Supreme Court, Criminal chamber General Prosecutor of the State Cándido Conde-Pumpido Tourón As jurists, lawyers, judges, academics (...)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Can labour officials seize records from your office? - Mugo, Jacqueline (Business Daily, 2010)
When can employment records be seized? Some employers have complained of labour officials asking them to submit these records to their offices for inspection.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Women's Rights in the United Arab Emirates (UAE) - International Federation for Human Rights (International Federation for Human Rights, 2010)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

International Convention for the Protection of All Persons from Enforced Disappearance - United Nations (OHCHR, 2010)
Entry into force: 23 December 2010, in accordance with article 39(1) which reads as follows: “This Convention shall enter into force on the thirtieth day after the date of deposit with the Secretary-General of the United Nations of the twentieth instrument of ratification or accession.”. Preamble The States Parties to this Convention,
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Unearthed: journal gives eye witness account of slavery - The Herald (HeraldScotland, 2010)
The account in the Scottish Catholic Archives underlines the complexity of Victorian attitudes towards race and slavery, hard on the heels of the historian Professor Tom Devine of Edinburgh University arguing that Scots have been guilty of collective amnesia over our involvement in slavery.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Human Rights Working Group - 2010-12 (December) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-11 (November) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-10 (October) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-09 (September) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-08 (August) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-07 (July) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-06 (June) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-05 (May) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-04 (April) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-03 (March) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-02 (February) - Peterson, Trudy Huskamp (ICA, 2010)

News from the ICA Human Rights Working Group - 2010-01 (January) - Peterson, Trudy Huskamp (ICA, 2010)